2007
DOI: 10.1103/physrevd.75.096004
|View full text |Cite
|
Sign up to set email alerts
|

BEC-BCS crossover in the Nambu-Jona-Lasinio model of QCD

Abstract: The BEC-BCS crossover in QCD at finite baryon and isospin chemical potentials is investigated in the Nambu-Jona-Lasinio model. The diquark condensation in two color QCD and the pion condensation in real QCD would undergo a BEC-BCS crossover when the corresponding chemical potential increases. We determined the crossover chemical potential as well as the BEC and BCS regions. The crossover is not triggered by increasing the strength of attractive interaction among quarks but driven by changing the charge density… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
134
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(140 citation statements)
references
References 83 publications
4
134
0
Order By: Relevance
“…Keeping it in mind that our concerned three-flavor superconductor is a fictional phase being valid near the flavor SU(3) limit, the magnitude of µ could not be identified with the baryon density of strongly interacting matter in realistic situations. In addition, strong coupling strength like G d /G s ∼ 1.1 − 1.5 had been used for studying quark superconducting phase and the BEC possibility in it [10,11,14,17]. There, exploring the BCS-BEC crossover physics was actually limited in the scope of strong-coupling quark superconductivity and the phase transition to the confined hadronic phase was not incorporated yet.…”
Section: The Unlocking Transition To 2scmentioning
confidence: 99%
See 1 more Smart Citation
“…Keeping it in mind that our concerned three-flavor superconductor is a fictional phase being valid near the flavor SU(3) limit, the magnitude of µ could not be identified with the baryon density of strongly interacting matter in realistic situations. In addition, strong coupling strength like G d /G s ∼ 1.1 − 1.5 had been used for studying quark superconducting phase and the BEC possibility in it [10,11,14,17]. There, exploring the BCS-BEC crossover physics was actually limited in the scope of strong-coupling quark superconductivity and the phase transition to the confined hadronic phase was not incorporated yet.…”
Section: The Unlocking Transition To 2scmentioning
confidence: 99%
“…BEC displays a strong correlation in the coordinate space whereas BCS does a strong correlation in the momentum space. The BCS-BEC crossover physics in the scope of quark color superconductivity has attracted much attention and been investigated by a variety of QCD models [9,10,11,12,13,14,15,16,17,18]. For the strong-coupling regime, people usually apply the phenomenological models such as the Nambu Jona-Lasinio (NJL) model with both quark-antiquark and quark-quark interactions.…”
Section: Introductionmentioning
confidence: 99%
“…On the example of the pion we will explain the physics of the Mott transition. The detailed investigation of the quantized diquark fluctuations, which are also a prerequisite of the formation of baryons, will be given elsewhere [30,35,36].…”
Section: Scalar-pseudoscalar Mesons In a Superconducting Two-flavor Nmentioning
confidence: 99%
“…Recently, this transition became accessible to laboratory experiments with ultracold gases of fermionic atoms coupled via Feshbach resonances with a strength tunable by applying external magnetic fields [24,25,26,27,28]. The BEC-BCS crossover transition in quark matter is of particular theoretical interest due to the additional relativistic regime it offers [9,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The properties of QC 2 D were studied theoretically within the following approaches: ChPT [2][3][4], the NJL model [5][6][7], FRG [8,9], random matrix theory [10][11][12]. Principally, these studies have revealed the following phase structure of low temperature QC 2 D with three subsequent phases: (1) 0 < µ < µ c (hadronic phase), (2) µ c < µ < µ d ("baryon onset" with a superfluid condensate due to Bose-Einstein condensation [BEC]) and (3) µ d < µ (the phase with diquark condensation due to the Bardeen-Cooper-Schrieffer mechanism [BCS] [13]).…”
Section: Introductionmentioning
confidence: 99%